Integration of Mobility Training in Physical Education Curriculum for Enhancing Selected Fitness Variables Among School Girls - Saranya, Ms S.; Shanmugavalli, Dr T.; A H, Dr. Radhika. (International Journal of Aquatic Research and Environmental Studies, 2026)
The study investigates the effects of mobility training on selected physiological variables, specifically flexibility, balance, and coordination, among adolescent schoolgirls aged 12-16. This research addresses a pressing issue: only 24% of adolescents meet recommended physical activity guidelines, with girls showing even lower participation levels. Mobility training, an innovative approach to fitness, enhances movement efficiency by combining flexibility, stabilization, and control. A randomized controlled trial design was employed, involving 40 participants divided into experimental and control groups. The experimental group undertook an 8-week mobility training database consisting of dynamic stretches, mobility drills, and functional movements for 30 minutes, five days a week. Pre-test and post-test assessments measured flexibility (Sit and Reach Test), balance (Flamingo Balance Test), and coordination (Alternative Hand Wall Toss Test). Results demonstrated significant improvements in the experimental group for flexibility (mean increase: 3.25 cm, t = 20.29), balance (mean increase: 4.65, t = 14.70), and coordination (mean increase: 4.15, t = 15.70). In contrast, the control group presented not at all statistically significant variations. The findings validate the efficacy of mobility training in enhancing physical attributes critical for motor performance and overall fitness. This research emphasizes the standing of integrating mobility training into school physical schooling plans to promote adolescent health and development. Recommendations include structured lesson plans, professional training for educators, besides policy guidelines to support systematic implementation. Further studies should explore long-term effects and additional benefits, such as mental health and injury prevention, to establish mobility training as an essential component of holistic education.
Keywords: mobility training, flexibility, balance, coordination and school girls